Using isotope dilution assays to understand speciation changes in Cd, Zn, Pb and Fe in a soil model system under simulated flooding conditions - Izquierdo, M.; Tye, A.M.; Chenery, S.R. (Elsevier, 2017)
Flooded soils are systems with complex chemistry and understanding the mechanisms that control the mobility and bioavailability of metals in these soils is important for their management. This work uses stable metal multi-element isotopic dilution combined with sequential extraction assays to help understand the changes in solid and solution speciation of Cd, Fe, Pb and Zn in a contaminated soil following submergence. However, it is necessary to ensure that the isotopic dilution principles, originally developed for aerobic soils, are not compromised; in particular due to the presence of non-labile colloids in the solution phase. In particular, no studies examining the validity of these assays in systems where rapid pH and Eh changes are occurring due to fermentation reactions have been published. Thus sucrose (0.42% and 1.26% added C) was used as a carbon source to stimulate bacterial mediated fermentation reactions allowing changes in Cd, Zn, Fe and Pb isotopic exchangeability, speciation and solution chemistry to be examined after 10, 20 and 42 days of submergence. Without the addition of added C, submergence for 42 days only produced minor changes in the speciation of the metals in solid or solution phases. However, the presence of easily labile carbon produced significant responses depending on the quantity of C added. Assessments of whether fermentation products caused over-estimation of the isotopically exchangeable pool of metals (E-values) were made by measuring concentrations with and without a resin purification step. Results showed generally good agreement over a pH range of 4–7 for Pb, Cd, Zn and Fe and demonstrate that fermentation by-products do not induce the formation of non-exchangeable metal colloids. E-value concentrations were compared with fractions extracted using a modified Tessier sequential extraction. With no carbonate phases present in the soils, the E-values for Cd, Zn, Fe and Pb compared favourably with the concentrations of metal present in the combined solution, exchangeable and specifically adsorbed fractions. This provided additional evidence that the conditions for the isotopic dilution assays were not violated as these fractions should be isotopically exchangeable. Combining results from the different treatments and stages of the reduction process, strong pH dependence was found for the isotopically exchangeable and the solution pools of Cd, Zn and Pb.